Usability and psychometric properties of a battery of tools to assess intelligence, executive functioning, and sustained attention in Tanzanian children. - Georg Loss; Hannah Cummins; Nicolaus Gutapaka; Jane Nyandele; Sylvia Jebiwott; Deborah Sumari; Thabit Athuman; Omary Juma; Susanne P Martin-Herz; Ally Olotu; Michelle S Hsiang; Günther Fink (PLoS ONE)
Background Measuring neurocognitive functioning in children requires validated, age-appropriate instruments that are adapted to the local cultural and linguistic context. We sought to evaluate the usability and psychometric properties of five tools that assess general intelligence, executive functioning, and sustained attention among Tanzanian children. Methods We adapted five age-appropriate neurocognitive assessment batteries from previously published assessment materials to the Tanzanian context. We enrolled children 6 months to 12 years of age residing in the rural ward of Yombo, Pwani Region. Feasibility and acceptability of all instruments was assessed qualitatively and quantitatively, including measurement of refusal rates, ceiling or floor effects, and time requirements. We assessed internal consistency using Cronbach's alpha and convergent validity using standard correlation analysis. Score gradients across age were explored using polynomial regression analysis. Findings All five instruments required minimal adaptations to the Tanzanian context. Two-hundred sixty one children aged 6 months to 12 years completed the assessment. Refusal rates were consistently low (5.9% at the highest) and no ceiling or floor effects of measurements were observed. Feedback from assessors and caregivers indicated adequate test durations and generally high acceptability of instruments. All instruments showed good internal consistency with Cronbach alphas at least 0.84 for all tests. We found satisfactory convergent validity; all test scores strongly correlated with age. Conclusion The five instruments identified to assess general intelligence, executive functioning, and sustained attention constructs in Tanzanian children seem to work well in this setting.